Prehospital anaesthesiologists experience with cardiopulmonary resuscitation-induced consciousness in Norway – A national cross-sectional survey - Jostein Rødseth Brede; Eivinn Årdal Skjærseth; Marius Rehn (Resuscitation Plus, 2024)
Background: During cardiopulmonary resuscitation (CPR) cerebral blood flow may be sufficient to restore some cerebral function, and CPR-induced consciousness (CPRIC) may occur. CPRIC includes signs of life such as gasping, breathing efforts, eye opening, movements of extremities or communication with the rescuers. There is a lack in evidence for prevalence, experience, and possible treatment strategies for CPRIC. This survey aimed to assess prehospital anaesthesiologists experience with CPRIC in Norway. Methods: A web-based cross-sectional survey. All physicians working at a Norwegian air ambulance, search-and-rescue base or physician-staffed rapid response car were invited to participate. Result: Out of 177 invited, 115 responded. All were anaesthesiologist, with mean 12.7 (SD 7.2) years of prehospital experience, and 25% had attended more than 200 out-of-hospital cardiac arrests (OHCA). CPRIC was known amongst most physicians prior to the survey and experienced by 91%. Mechanical compression device was used in 79% of cases. The CPRIC were CPR-interfering in 31% of cases. Next-of-kin reported the CPRIC as upsetting in 5% of cases. Medication and/or physical restraint were administered in 75% patients. For patients with CPRIC 50% answered that sedation was needed. If sedation should be provided, 62% answered that this should only be performed by a physician, while 25% answered that both ambulance crew and physicians could provide sedation. Fentanyl, ketamine, and midazolam were suggested as the most appropriate sedation agents. Conclusion: This nationwide survey indicates that CPRIC during OHCA are well known amongst prehospital anaesthesiologist in Norway. Most patients with CPRIC were treated with chest compression device. Most physicians recommend sedation of patients with CPRIC during resuscitation.